Solving Bi-harmonic Cauchy problem using a meshless collocation method - Khaleel Mostafa, Baydaa; Jasim , Duaa; Falih Hasan , Athraa; Thabit Jameel, Ibtihal; M. ABOUD, Fatima (ASJ - Academic Science Journal, 2024)
In this article a fourth order differential boundary value problem is solved using a mesh less collocation method. The efficiency of the proposed methods is illustrated by solving problems with some examples of a polynomial and Non polynomial exact solutions and by using Conjugate gradient method and Conjugate gradient Least square algorithms and the numerical stability is verified by using a noise for the input boundary data.